The âThaharah Bermaknaâ Training Through The Logo Analysis Model to Build Studentsâ Positive Characters - Nurjannah, Nurjannah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This experimental study aimed to investigate the effect of the âthaharah bermaknaâ (meaningful purification)â through the logo analysis model to build studentsâ positive characters. The experiment employed the one-group pretest-posttest design involving 22 students of SMP Diponegoro Yogyakarta. The data were collected through a positive character scale (riÂ = 0.316-0.651, Î± = 0.929) and a monitoring sheet for the âthaharah bermaknaâ independent practice. The results of the within subject test showed that the âthaharah bermaknaâ training and the independent practice for a week were capable of significantly improving studentsâ positive characters with F = 0.578, p = 0.005 (p<0.010). Before the treatment, the subjectsâ mean score was 186.91 and after the treatment their mean score improved to 193.91. The study concluded that the âthaharah bermaknaâ training through the logo analysis model and an independent practice for a week significantly improved studentsâ positive characters. In other words, it could be said that the âthaharah bermaknaâ training was effective to build studentsâ positive characters.Â ——-Penelitian eksperimen ini bertujuan untuk melihatÂ pengaruh pelatihan âthaharah bermaknaâ menggunakan model logoanalisis untuk membentuk karakter positif siswa. Eksperimen menggunakan desain tes awal-tes akhir satu kelompok eksperimen ini melibatkan 22 siswa SMP Diponegoro Yogyakarta. Data dikumpulkan dengan menggunakan skala karakter positif (ri=0,316-0,651, Î±=0,929) dan lembar monitor praktek mandiri âthaharah bermaknaâ. Hasil uji with-in subject menunjukkan bahwa pelatihan âthaharah bermaknaâ dan praktek mandiri selama satu minggu, signifikan meningkatkan karakter positif siswa dengan t=0,578 p=0,005 (p<0,010). Sebelum diberi perlakuan, skor rerata subjek sebesar 186,91 dan setelah diberi perlakuan skor rerata subjek meningkat menjadi 193,91. Dalam kajian ini disimpulkan bahwa pelatihan âthaharah bermaknaâ dengan menggunakan model logoanalisis dan praktek mandiri selama satu minggu signifikan meningkatkan karakter positif siswa. Dengan demikian dapat dikatakan bahwa âthaharah bermaknaâ efektif digunakan untuk membentuk karakter positif siswa.Â Â